2005
DOI: 10.1590/s1413-86702005000400001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and hemodialysis: a review

Abstract: Hepatitis C is a serious public health problem throughout the world; chronic renal patients are highly exposed to this infection. This could be due to a failure to identify carriers of this disease or because of a lack of truly effective biosafety measures implemented in the dialysis units. Molecular biology techniques have allowed for the understanding of this virus in detail, including its replication mechanisms. Epidemiological studies have been made throughout the world, with the goal of determining the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Data from 8,615 patients in hemodialysis units screened for HCV in seven countries revealed the presence of the virus in a mean of 13.5%, ranging from 2.6% in the United Kingdom to 22.9% in Spain; the rate in U.S. units was 14.9% 235. Even higher rates have been reported from dialysis units in some developing countries 238, 239. A national survey in U.S. dialysis centers in the year 2000 found anti‐HCV to be present in 8.4% of patients and in 1.7% of staff 237.…”
Section: Special Patient Groupsmentioning
confidence: 99%
“…Data from 8,615 patients in hemodialysis units screened for HCV in seven countries revealed the presence of the virus in a mean of 13.5%, ranging from 2.6% in the United Kingdom to 22.9% in Spain; the rate in U.S. units was 14.9% 235. Even higher rates have been reported from dialysis units in some developing countries 238, 239. A national survey in U.S. dialysis centers in the year 2000 found anti‐HCV to be present in 8.4% of patients and in 1.7% of staff 237.…”
Section: Special Patient Groupsmentioning
confidence: 99%
“…A recent review also showed that Italy and France had a prevalence of HCV in dialysis patients of 20.5% and 10.4%, respectively [Prati, 2006]. In Brazil, the prevalence is even higher, ranging from 35.5% in the Southeast region to 45.5% in the Northern region [Moreira et al, 2005]. Extremely high prevalences of 94.7% have been reported from Saudi Arabia [Huraib et al, 1995] and from Moldavia with 75% [Covic et al, 1999].…”
Section: Discussionmentioning
confidence: 98%
“…[11] Hence, although the potential sources of nosocomial transmission could be dialyzer reuse, internal contamination of HD monitors, environmental aerosols, droplets contaminated with the virus and contaminated hands and articles, the two former mechanisms are almost unlikely. [12] The performance parameters of the testing method used have a direct impact on the detection of hepatitis C and thus can lead to differences in the prevalence data.…”
Section: Discussionmentioning
confidence: 99%